PECULIARITIES OF CULTIVATION OF HAEMOPHILUS INFLUENZAE TYPE B STRAINS - PRODUCERS OF POLYRIBOSYLRIBITOL PHOSPHATE - THE MAIN COMPONENT OF POLYSACCHARIDE VACCINES - E. L. Salimova; A. D. Konon; S. V. Petrovskii; V. P. Truhin; I. V. Krasilnikov (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2017)
One of the up-to-date challenges of modern immunobiotechnology is the development and introduction of an effective vaccine against the infection caused by the bacterium Haemophilus influenza, type b (Hib). The main active substance of the vaccine against Hib infection is the capsular polysaccharide polyribosylribitol phosphate (PRP), which is isolated from the fermentation broth of H. influenzae type b. An important technological step in obtaining PRP is the cultivation of the producer strain under conditions that allow obtaining the maximum amount of the target product. At the moment, it is planned to select the optimal conditions for cultivation of H. influenzae type b B-7884, which had been earlier isolated and identified by the employees of FSUE "Saint-Petersburg scientific research institute of vaccines and serums and the enterprise for the production of bacterial preparations" of FMBA, Russia. The analysis of literature data concerning the cultivation of H. influenzae type b was made in order to identify the main factors influencing the biosynthesis of PRP.The aim of the investigation is to analyze and summarize the literature data on the cultivation peculiarities of haemophilus influenzae of b-type strains.Materials and methods. In the process of selecting the material for writing this review article. The databases of Google Patents, Science Research Portal, Google Scholar, ScienceDirect, CiteSeer Publications ResearchIndex, Ingenta, PubMed, KEGG, etc. were used.Results and discussion. As a result of the literature analysis, the main factors influencing the PRP biosynthesis were identified: the nature and concentration of carbon and nitrogen sources in the growth medium, the concentration of growth factors (nicotinamide adenine dinucleotide, hemin, vitamins), additional feed, pH adjustment during cultivation, stirring speed. The data of PRP-producing strains and the conditions of their cultivation have been summarized, as well as the amount of synthesized PRP, which essentially depends on both the physiological capabilities of the biological agent and the factors effecting the regulation of metabolism.Conclusion. The results of this work will be taken into account in carrying out the researches for optimization of H. influenzae type b B-7884 strain cultivation conditions.